Case Report: An Atypical Presentation of Panic Disorder Masquerading as Possession Trance - Khoe, Howard C. H.; Gudi, Alakananda (Frontiers in Psychiatry, 2022)
This case report demonstrates an atypical presentation of panic disorder which masqueraded as episodes of possession trance. Patient X is a 62-year-old Chinese female who presented with recurrent episodes of uncontrollable screaming and shaking of all four limbs. During these episodes, she reported auditory hallucinations (Buddhist chanting) and visual hallucinations (a rotting corpse) which she attributed to the influence of “evil spirits.” She was diagnosed with panic disorder with culture-specific symptoms on a background of major depressive disorder. With an understanding of the patient's belief system and an empathetic approach during psychoeducation, she eventually accepted the use of pharmacotherapy. She was prescribed escitalopram (started at 2.5 mg OM) and clobazam (10 mg ON) with good clinical effect and cessation of episodes afterward.